(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Background: Cervical cancer is 4th most common cancer in women in the world and the most common form of cancer in women in developing countries. Population based cervical cancer screening and treatment of intraepitheial neoplasia in early stage can reduce morbidity and mortality associated with cervical cancer. To determine the prevalence of cervical intra epithelial neoplasia (CIN) among sexually active and married women in Rajshahi Division of Bangladesh. Place and Duration: This population based cross sectional study was carried out in 4 selected Upazilla from 4 different districts of Rajshahi Division from 1st December 2014 to 31st May 2015. Study on 1050 sexually active women between 25 to 55 years of age who fulfilled the inclusion criteria enrolled in the study after taking the consent. Result: Among 1050 enrolled women 90 (8.5%) were VIA positive and 91 were colposcopically abnormal and among them 33 were CIN positive & 58 had chronic cervictis with or without squamorus metaplasia. Mean age of CIN positive women was 36.75 years, 92.2% were housewife & 7.8% were service holder and in 64.6% women education level was up to XII class. In fifty five percent of their husband was day labouer from poor socioeconomic condition. Conclusion: VIA and Colopscopy can differentiate a normal cervix from a precancerous cervix with reasonable accuracy. Till now a good number of studies had been carried out in different countries of world and it is now well established that sensitivity of the test is very good. From the present study we can conclude that it will give a very good information about the prevalence of CIN in our country and by proper management of the CIN cases the incidence of carcinoma cervix can be reduced. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 17-20